Peculiarities of Motor Abilities Development in 7th-8th-Graders - Мороз, Ю. В. (Physical Education Theory and Methodology, 2015)
The pupose of the research is to define the peculiarities of motor abilities development in children of middle-school age. Research methods: theoretical analysis and collation of scientific and methodological literature; pedagogical testing; methods of mathematical statistics. To determine the effectiveness of realization of the developmental task of the physical education process at the beginning of the school year (in October 2014) and in March 2015, we tested the level of development of physical qualities in the 7th- and 8th-graders, 25 and 25 graders respectively, 13 of which in each class were boys and 12 — girls. Research results. The analysis of the materials shows that during the school year, the boys of the 7th grade showed reliably increased performance in standing long jumps (speed and strength qualities) — 1.97%, raising the body from the lying position (strength) — 26.46%, bent suspension (strength) — 13.45%. The indicators have insignificantly (unreliably) increased in the shuttle run 3×10 m (agility) — 6.09%, and in body bending from the sitting position (flexibility) — 6.25%. The girls showed reliably increased performance in the level of readiness: flexibility — 12%, strength — 12.09%, speed-strength qualities — 5.27%, agility — 7.77%. The analysis of the materials shows that during the school year the 8th-graders (boys) reliably increased their physical readiness in speed-strength qualities — 0.8%, strength — 15.7%. The indicators of agility increased unreliably — 2.7%, as well as those of flexibility — 8%. The 8th‑graders (girls) reliably improved their indicators in standing long jumps — 2.1%, in bent suspension — 18.8%, raising the body from the lying position in 30 seconds — 17.4%, body bending from the sitting position — 12 5%. The indicators agility improved unreliably — 3.4%. Conclusions. The data obtained are important in solving the pedagogical problems of schoolers’ physical education as decisions of the matters of principle in organization and methods used in physical training classes rest on the ideas about the regularities of the age-related development and the effects of physical exercises.